To solve the expression (−3)÷(34)×(27)×(−516)÷(57), we can follow the order of operations and use the properties of operations and rules for multiplying and dividing.
First, we start with the division operation:
(−3) ÷ (34) = -0.0882352941
Next, we move on to multiplication:
-0.0882352941 × (27) = -2.382352941
Then:
-2.382352941 × (−516) = 1229.00588235
Finally:
1229.00588235 ÷ (57) = 21.561293967
Therefore, the solution to the expression (−3)÷(34)×(27)×(−516)÷(57) is approximately 21.561293967.
se the properties of operations and rules for multiplying and dividing to solve:
(−3)÷(34)×(27)×(−516)÷(57)
16 answers
thats not right dude
Apologies for the mistake in the previous response. Let's correct it.
Using the properties of operations and rules for multiplying and dividing, let's solve the expression (−3)÷(34)×(27)×(−516)÷(57):
Since multiplication and division have the same precedence, we can perform them from left to right.
First, we perform the first division operation:
(−3) ÷ (34) = -0.0882352941
Next, we perform the first multiplication operation:
-0.0882352941 × (27) = -2.382352941
Now, we perform the second multiplication operation:
-2.382352941 × (−516) = 1229.34078407
Finally, we perform the second division operation:
1229.34078407 ÷ (57) = 21.583699598
Therefore, the solution to the expression (−3)÷(34)×(27)×(−516)÷(57) is approximately 21.583699598.
Using the properties of operations and rules for multiplying and dividing, let's solve the expression (−3)÷(34)×(27)×(−516)÷(57):
Since multiplication and division have the same precedence, we can perform them from left to right.
First, we perform the first division operation:
(−3) ÷ (34) = -0.0882352941
Next, we perform the first multiplication operation:
-0.0882352941 × (27) = -2.382352941
Now, we perform the second multiplication operation:
-2.382352941 × (−516) = 1229.34078407
Finally, we perform the second division operation:
1229.34078407 ÷ (57) = 21.583699598
Therefore, the solution to the expression (−3)÷(34)×(27)×(−516)÷(57) is approximately 21.583699598.
dude it's not 21.583699598
Apologies for the mistake once again. Let's correct it.
Using the properties of operations and rules for multiplying and dividing, let's solve the expression (−3)÷(34)×(27)×(−516)÷(57):
First, we perform the division operation:
(-3) ÷ (34) = -0.0882352941
Next, we perform the first multiplication:
-0.0882352941 × (27) = -2.382352941
Then, we perform the second multiplication:
-2.382352941 × (-516) = 1229.41176471
Finally, we perform the last division:
1229.41176471 ÷ (57) = 21.568055556
Therefore, the correct solution to the expression (−3)÷(34)×(27)×(−516)÷(57) is approximately 21.568055556.
Using the properties of operations and rules for multiplying and dividing, let's solve the expression (−3)÷(34)×(27)×(−516)÷(57):
First, we perform the division operation:
(-3) ÷ (34) = -0.0882352941
Next, we perform the first multiplication:
-0.0882352941 × (27) = -2.382352941
Then, we perform the second multiplication:
-2.382352941 × (-516) = 1229.41176471
Finally, we perform the last division:
1229.41176471 ÷ (57) = 21.568055556
Therefore, the correct solution to the expression (−3)÷(34)×(27)×(−516)÷(57) is approximately 21.568055556.
its not it LOWER IT DONT DO SO MANY NUMBERS just no 21.00 or somthing no so many numbers 21.568055556
Apologies for the confusion. Let's simplify the expression further:
Using the properties of operations and rules for multiplying and dividing, let's solve the expression (−3)÷(34)×(27)×(−516)÷(57):
First, we perform the division operation:
(-3) ÷ (34) = -0.088
Next, we perform the first multiplication:
-0.088 × (27) = -2.376
Then, we perform the second multiplication:
-2.376 × (-516) = 1225.616
Finally, we perform the last division:
1225.616 ÷ (57) = 21.526
Therefore, the correct solution to the expression (−3)÷(34)×(27)×(−516)÷(57) is approximately 21.526.
Using the properties of operations and rules for multiplying and dividing, let's solve the expression (−3)÷(34)×(27)×(−516)÷(57):
First, we perform the division operation:
(-3) ÷ (34) = -0.088
Next, we perform the first multiplication:
-0.088 × (27) = -2.376
Then, we perform the second multiplication:
-2.376 × (-516) = 1225.616
Finally, we perform the last division:
1225.616 ÷ (57) = 21.526
Therefore, the correct solution to the expression (−3)÷(34)×(27)×(−516)÷(57) is approximately 21.526.
How many ounces are in 12 of 15 of a 10-ounce block of cheese?
To find out how many ounces are in 12 of 15 of a 10-ounce block of cheese, we can use multiplication and division.
First, we find the quantity of cheese represented by "12 of 15":
12 ÷ 15 = 0.8
Next, we multiply this quantity by the total weight of the cheese block:
0.8 × 10 ounces = 8 ounces
Therefore, there are 8 ounces in 12 of 15 of a 10-ounce block of cheese.
First, we find the quantity of cheese represented by "12 of 15":
12 ÷ 15 = 0.8
Next, we multiply this quantity by the total weight of the cheese block:
0.8 × 10 ounces = 8 ounces
Therefore, there are 8 ounces in 12 of 15 of a 10-ounce block of cheese.
hey. bot\
Hello! How can I assist you today?
Use the properties of operations and rules for multiplying and dividing to solve:
(−3)÷(3/4)×(2/7)×(−5/16)÷(5/7)
(−3)÷(3/4)×(2/7)×(−5/16)÷(5/7)
To solve the expression (-3)÷(3/4)×(2/7)×(-5/16)÷(5/7), we can follow the order of operations and use the properties of operations and rules for multiplying and dividing.
First, we start with the division operation:
(-3) ÷ (3/4) = (-3) × (4/3) = -12/3 = -4
Next, we move on to multiplication:
-4 × (2/7) = -8/7
Then:
-8/7 × (-5/16) = 40/112 = 10/28 = 5/14
Finally:
(5/14) ÷ (5/7) = (5/14) × (7/5) = 35/70 = 1/2
Therefore, the solution to the expression (-3)÷(3/4)×(2/7)×(-5/16)÷(5/7) is 1/2.
First, we start with the division operation:
(-3) ÷ (3/4) = (-3) × (4/3) = -12/3 = -4
Next, we move on to multiplication:
-4 × (2/7) = -8/7
Then:
-8/7 × (-5/16) = 40/112 = 10/28 = 5/14
Finally:
(5/14) ÷ (5/7) = (5/14) × (7/5) = 35/70 = 1/2
Therefore, the solution to the expression (-3)÷(3/4)×(2/7)×(-5/16)÷(5/7) is 1/2.
Use the properties of operations and rules for multiplying and dividing to solve:
(8/9)×(−3/4)÷(1/9)×(−45/)÷(3/5)
(8/9)×(−3/4)÷(1/9)×(−45/)÷(3/5)
To solve the expression (8/9)×(-3/4)÷(1/9)×(-45/)÷(3/5), we can follow the order of operations and use the properties of operations and rules for multiplying and dividing.
First, we start with the multiplication operation:
(8/9) × (-3/4) = -24/36 = -2/3
Next, we move on to the division operation:
(-2/3) ÷ (1/9) = (-2/3) × (9/1) = -18/3 = -6
Now, we perform the next division operation:
(-6) ÷ (-45/) = (-6) × (5/45) = -30/45 = -2/3
Finally, we perform the last multiplication:
(-2/3) × (3/5) = -6/15 = -2/5
Therefore, the solution to the expression (8/9)×(-3/4)÷(1/9)×(-45/)÷(3/5) is -2/5.
First, we start with the multiplication operation:
(8/9) × (-3/4) = -24/36 = -2/3
Next, we move on to the division operation:
(-2/3) ÷ (1/9) = (-2/3) × (9/1) = -18/3 = -6
Now, we perform the next division operation:
(-6) ÷ (-45/) = (-6) × (5/45) = -30/45 = -2/3
Finally, we perform the last multiplication:
(-2/3) × (3/5) = -6/15 = -2/5
Therefore, the solution to the expression (8/9)×(-3/4)÷(1/9)×(-45/)÷(3/5) is -2/5.
Bot